Optimisation Algorithms and Swarm Intelligence (IntechOpen, 2022)
Optimisation is one of the unavoidable key subjects in engineering and other real-world problems, which attracts researchers’ and practitioners’ attention for decades. On the other hand, computational algorithms nowadays play a definitive role in most real-life applications, from mobile phones to supercomputers, Internet servers, manufacturing, etc. An intelligent method for the enumeration of feasible solutions may lead to efficient computational algorithms. Swarm intelligence emerges as a rather new and novel of field computational intelligence that turned into a hot spot in optimization studies last two decades. This book brings together a number of research articles within the intersection of these two prominent subjects, which introduces techniques and approaches in detail and demonstrates how optimisation problems can be solved with heuristic and swarm intelligence approaches. It contains a few contributions on Particle Swarm Optimisation (PSO) area, which is one of renown swarm optimisation approaches that will shed light to issues around optimisation with swarm intelligence to guide junior researchers with implementation details provided.